2016
DOI: 10.22518/16578953.534
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias de desarrollo rural con enfoque de género en Chile: el caso del programa “Formación y capacitación para mujeres campesinas”

Abstract: La agricultura familiar campesina presenta limitaciones en sus capacidadesproductivas, las cuales se acentúan en el caso de las mujeres jefas deexplotación, situación cada vez más frecuente en países de América Latinacomo Chile. En este contexto, el presente artículo tiene como objetivo analizarel caso específico del programa “Formación y capacitación para mujerescampesinas” del Instituto de Desarrollo Agropecuario de Chile, ejecutado enconvenio con la Fundación para la Promoción y el Desarrollo de la Mujer. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Therefore, the lack of time, due to a work overload, and training for rural women could be limiting their capabilities to manage BPS when compared to men, leaving time for only basic management, such as feeding and releasing/enclosing animals and resulting in reduced or absent biosecurity and hygiene measures. Further data supports gender inequality in rural areas; i.e., the percentage of illiteracy in rural women (70+ years of age) of Chile was over 35% and labor force participation rate for rural women was of 19%, 48 percentage points less than rural men and 19 percentage points less than urban women [83,84]. Currently, in the forestry and livestock sector, the percentage of employed women corresponds to 24.2% of the total number of workers, almost 52 percentage points below that of rural men [81].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Therefore, the lack of time, due to a work overload, and training for rural women could be limiting their capabilities to manage BPS when compared to men, leaving time for only basic management, such as feeding and releasing/enclosing animals and resulting in reduced or absent biosecurity and hygiene measures. Further data supports gender inequality in rural areas; i.e., the percentage of illiteracy in rural women (70+ years of age) of Chile was over 35% and labor force participation rate for rural women was of 19%, 48 percentage points less than rural men and 19 percentage points less than urban women [83,84]. Currently, in the forestry and livestock sector, the percentage of employed women corresponds to 24.2% of the total number of workers, almost 52 percentage points below that of rural men [81].…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, it is estimated that the average number of hours worked by rural women was 13 h/day, both inside and outside the home [81]. Additionally, in the forestry and livestock sector, it has been found that women have lesser access to training [82][83][84]. Therefore, the lack of time, due to a work overload, and training for rural women could be limiting their capabilities to manage BPS when compared to men, leaving time for only basic management, such as feeding and releasing/enclosing animals and resulting in reduced or absent biosecurity and hygiene measures.…”
Section: Discussionmentioning
confidence: 99%
“…Esta especie es de alto valor genético, económico, nutricional y patrimonial, y es empleada ancestral, cultural y tradicionalmente por comunidades rurales que fundamentan la producción de sus alimentos en base a sistemas sustentables, de bajo impacto ambiental, respetuosos con el bienestar animal, a la vez que resguardan la economía familiar, la seguridad y soberanía alimentarias (FAO, 2013;Boza et al, 2016;FAO, 2023).…”
Section: Introductionunclassified